2017
DOI: 10.1098/rstb.2016.0248
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiology of interspecific interactions in a changing world

Abstract: Animals should time activities, such as foraging, migration and reproduction, as well as seasonal physiological adaptation, in a way that maximizes fitness. The fitness outcome of such activities depends largely on their interspecific interactions; the temporal overlap with other species determines when they should be active in order to maximize their encounters with food and to minimize their encounters with predators, competitors and parasites. To cope with the constantly changing, but predictable structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 173 publications
0
72
0
Order By: Relevance
“…Circadian time-place learning, highlighted in this issue for bees [17], may enable kestrels to optimize their hunting behaviour. This example demonstrates the interactions of biological clocks with abiotic and biotic components of time, underlining the relevance of precise timing mechanisms [32].…”
Section: 'Wild Clocks': Time's Many Components Affect Organisms In Namentioning
confidence: 91%
See 2 more Smart Citations
“…Circadian time-place learning, highlighted in this issue for bees [17], may enable kestrels to optimize their hunting behaviour. This example demonstrates the interactions of biological clocks with abiotic and biotic components of time, underlining the relevance of precise timing mechanisms [32].…”
Section: 'Wild Clocks': Time's Many Components Affect Organisms In Namentioning
confidence: 91%
“…Animals live in a world where the abundance of resources and the incidence of threats fluctuate on daily, seasonal and potentially further temporal scales. In addressing these problems, the field of ecology has focused on the timing of individuals relative to the external environment, and on its consequences at intraspecific and interspecific levels [32,55]. The importance of cyclic repeatable variability in ecological conditions has been realized for a long time, and has been highlighted by phenology studies that reported species-specific patterns, which sometimes were stunningly precise between years [29].…”
Section: (B) Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…Devils are both predators and highly-adapted scavengers, one of the world's few bone-specialist carnivores (Jones 2003). For example, kestrels Falco tinnunculus match the regular 2-h peaks in vole Microtus arvalis activity (Rijnsdorp et al 1981, Kronfeld-Schor et al 2017) and activity patterns of Cooper's hawk Accipiter cooperii reflects those of their prey (Roth and Lima 2007). Other studies show that predators can time their activity to overlap with peak prey activity.…”
Section: Carnivore Responses and Competitionmentioning
confidence: 94%
“…Declining predator densities may therefore elicit a more gradual response because persistence of low-cost behaviours can be adaptive even when selection is relaxed (Flecker 1992, Kronfeld-Schor et al 2017. First, the costs associated with increasing top-predator densities (death or injury) are probably much higher than the costs associated with decreasing predator densities (small potential foraging loss).…”
Section: Subtle and Variable Responses By Preymentioning
confidence: 99%